AN ANTI PIGMENTATION STICK- THE NOVEL AND INNOVATIVE FORMULATION - Shruti Manoj Shinde; Supriya Prabhakar Dhole; Raj Prashant Udamale; Ganesh Sanjay Randhave; Subhash Khanderao Bhore; Aniket Dnyandev Najan; Gaurav Santosh Waykar; Rutuja Devidas Lagad; Ankita Arjun Giramkar; Dr. Amol Navnath Khedkar (The Bioscan, 2026)
Hyperpigmentation is a common dermatological concern caused by excessive melanin production due to factors such as sun exposure, hormonal imbalance, inflammation, and aging. The present study aimed to formulate and evaluate an anti-pigmentation herbal stick using natural and synthetic depigmenting agents for convenient topical application and improved patient compliance. The formulation was developed using licorice root extract (Glycyrrhiza glabra) and kojic acid as the primary active ingredients because of their well-known skin-brightening and melanin-inhibiting properties. The anti-pigmentation stick was prepared using beeswax and stearic acid as structuring agents, while aloe butter and shea butter were incorporated to provide moisturization and skin nourishment. MCT oil and almond oil were used as emollients to enhance spreadability and improve skin conditioning. Arrowroot powder was added to impart a smooth texture and reduce greasiness. Vitamin E oil served as an antioxidant to protect the formulation from oxidative degradation, and phenoxyethanol was used as a preservative to ensure microbial stability.